Respuesta :

Wolfyy

First, lets write an expression.

(-4+6x)/33 = 20/15

~Now, solve for x.

(-4+6x) * 15 = 33 * 20

-60 + 90x = 660

-60 + 60 + 90x = 660 + 60

90x = 720

90x/90 = 720/90

x = 8

Best of Luck!

Answer:

x = 8

Step-by-step explanation:

Step 1:  Make an equation

[tex]\frac{(-4 + 6x)}{33} = \frac{20}{15}[/tex]

Step 2:  Cross multiply

[tex]\frac{(-4 + 6x)}{33} = \frac{20}{15}[/tex]

To cross multiply you multiply the first fraction top by the second fraction's bottom.  Next you multiply the first fraction bottom by the second fraction's top.

(-4 + 6x) * 15 = (20) * (33)

-60 + 90x = 660

Step 3:  Add 60 from both sides

-60 + 90x + 60 = 660 + 60

90x = 720

Step 4:  Divide both sides by 90

90x / 90 = 720 / 90

x = 8

Answer:  x = 8